The art of Linux Kernel Design : illustrating the operating system design principle and implementation /: illustrating the operating system design principle and implementation. (2018) - Yang, Lixiang; Wenfeng, Liang; Dazhou, Chen; Tianhou, Liu; Ruobing, Wu; Qi, Song; Ke, Feng
No abstract available